IMPLEMENTASI DIORAMA 3D INTERAKTIF BERBASIS PILAR (Dio- 3D IBP) DALAM MENINGKATKAN SELF MANAGEMENT DAN BLOOD PRESSURE CONTROL PADA PENDERITA HIPERTENSI - Fajriyah, Novita; Susanti, Susanti; Iswati, Iswati; Geonarso, Roberto (Community Development in Health Journal, 2024)
Introduction & Aim: Hypertension is a chronic disease and is considered a global health problem that can cause complications, such as cardiovascular disease, chronic kidney disease, dementia, and death from cardiovascular disease. Patients need a support system in managing their disease. One way to control blood pressure and prevent hypertension complications is to improve self-management. Community involvement is integrated in the program to have a social support system in carrying out self-management. The aim of this community service is to improve self-management and blood pressure control in hypertension sufferers. Method of Activity: Implementation of the Pillar-Based Interactive 3D Diorama (Dio-3D IBP) was carried out on 20 hypertensive respondents who had previously undergone examinations at the Surabaya regional health center. The community service lasted for four weeks in RW 07, Kapasan Village, Simokerto District, Surabaya. The activity stages are initial survey, implementation, education, mentoring and evaluation. Self management was measured using the Hypertension Self Management Behavior Questionnaire and blood pressure control was measured using a sphygmomanometer. Community service results are assessed by analyzing data using the Wilcoxon Signed Rank Test statistical test. Results: This community service can change people's behavior regarding self-management and blood pressure control. The results of the Wilcoxcon test are self-management p=0.001 and improvement in blood pressure with systole and diastole values p=0.00. Discussion: Implementation of a Pillar-Based Interactive 3D Diorama (Dio-3D IBP) can improve self-management and blood pressure control in hypertension sufferers. Health care workers should participate in health education programs to meet community needs and improve compliance with their treatment regimens.